Pengaruh Pengawasan dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Pada Dinas Lingkungan Hidup Kota Bima - Sahrun Hasan; Rahmatia; Firmansyah Kusumayadi (Journal of Mandalika Literature, 2024)
The existence of work enthusiasm can be reflected if employees feel happy with their work, employees will pay more attention and be more skilled in doing their work. Work enthusiasm can be reflected if employees feel happy with their work, employees will pay more attention and be more skilled in doing their work. Every government agency requires supervision from the leadership. This supervision is carried out by the leadership as an effort to compare whether it is being carried out in accordance with the plan being implemented. This also means that supervision is the action or activity of the leader who ensures that work is carried out in accordance with the plans set or the desired work results. This research aims to determine the effect of supervision and work environment on employee morale. The sample in this research was 30 ASNs using a purposive sampling technique. Data collection techniques using observation, questionnaires and literature study. The data analysis technique uses multiple linear regression assisted by SPSS for widows. The results of the research show that supervision and the work environment have a significant effect on the work morale of Bima City Environmental Service Employees.